Intravenous Enoxaparin Versus Unfractionated Heparin in Elderly Patients Undergoing Primary Percutaneous Coronary Intervention: An Analysis of the Randomized ATOLL Trial. (January 2017) - Liu, Zhenyu; Silvain, Johanne; Kerneis, Mathieu; Barthélémy, Olivier; Payot, Laurent; Choussat, Rémi; Sabouret, Pierre; Cohen, Marc; Pollack, Charles V.; Goldstein, Patrick; Zeymer, Uwe; Huber, Kurt; et al.
Elderly (≥75 years old) patients with ST-segment elevation myocardial infarction (STEMI) have higher ischemic and bleeding risk compared with those <75 years old. We investigated the efficacy and safety of intravenous (IV) enoxaparin versus IV unfractionated heparin (UFH) in elderly patients undergoing primary percutaneous coronary intervention (PCI) for STEMI. A prespecified analysis of the Acute Myocardial Infarction Treated with Primary Angioplasty and Intravenous Enoxaparin or Unfractionated Heparin to Lower Ischemic and Bleeding Events at Short- and Long-term Follow-up (ATOLL) study was performed examining the 30-day outcomes in the elderly patients. Of the 165 elderly patients in the ATOLL study, 85 patients received IV enoxaparin 0.5 mg/kg and 80 patients received IV UFH. Intravenous enoxaparin did not reduce the primary end point, the main secondary efficacy end point, major bleeding, major or minor bleeding, and all-cause mortality compared with IV UFH. The rate of minor bleeding (5.9% vs 22.8%, P adjusted = .01) was significantly lower with IV enoxaparin compared with IV UFH. Intravenous enoxaparin appears to be a safe alternative to IV UFH in primary PCI of the elderly patients with STEMI.